THE GENUS BORASSODENDRON (PALMAE) IN MALESIA - Dransfield, J. (REINWARDTIA, 1972)
In April 1968 while I was botanising in the Fourth Division of Sarawak, I was shown by Mr. David Senada, District Forest Officer, Bintulu, a tall fan palm growing by the new Bintulu to Miri road, about 15 km from Bintulu.